Online remaining lifetime estimation for structures. (15th March 2019) - Heinrich, C.; Khalil, M.; Martynov, K.; Wever, U.
Highlights: Online, real-time prediction of lifetime during operating of machinery. Model-order reduction for stresses. Moving-window online cycle counting. Algorithms tested for accuracy and speed on demonstrative example. Abstract: Consumed life time monitoring of a structure during operation is a topic of increasing interest. For applying the common Wöhler technique in real time, fast and accurate computation of stress is required. Within this paper we present an approach for computation of stress that is based on common model order reduction techniques. The performance of the method is demonstrated for several possible application scenarios. Linear and nonlinear structural mechanical equations are considered.